Republic of noise : the loss of solitude in schools and culture - Senechal, Diana (Lanham, Md. : Rowman & Littlefield Education, 2012)
"In this book, Diana Senechal confronts a culture that has come to depend on instant updates and communication at the expense of solitude. Schools today emphasize rapid group work and fragmented activity, not the thoughtful study of complex subjects. The Internet offers contact with others throughout the day and night; we lose the ability to be apart, even in our minds. Yet solitude plays an essential role in literature, education, democracy, relationships, and matters of conscience. Throughout its analyses and argument, the book calls not for drastic changes but for a subtle shift: an attitude that honors solitude without descending into dogma"--Provided by publisher.
Introduction: the chatter of the present -- Definitions of solitude -- Distraction: the flip side of engagement -- Antigone: literature as "thinking apart" -- The workshop model in New York City -- The folly of the "big idea" -- The cult of success -- Mass personalization and the "underground man" -- The need for loneliness -- The practice of solitude -- Discernment and the public sphere -- Conclusion: setting up shop.
Includes bibliographical references and index.
Keywords: Reflective learning; Classroom environment; Education -- Effect of technological innovations on; Solitude; EDUCATION -- Educational Policy & Reform -- General; BODY, MIND & SPIRIT -- General; EDUCATION -- General; EDUCATION -- Philosophy & Social Aspects; FAMILY & RELATIONSHIPS -- General; SOCIAL SCIENCE -- General; SOCIAL SCIENCE -- Popular Culture; Classroom environment; Education -- Effect of technological innovations on; Reflective learning; Solitude; Lernumwelt; Schulklima; 0